Implementation of a Soap Mixer Machine and Digital Accounting at the Uswah Hasanah Tahfizh School - Riaty HANDAYANI; Hari SETYAWATI; Swandya Eka PRATIWI; Aryo WICAKSONO; Rasyid ALAMSYAH (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This PKM activity was carried out by the UMB team with the Ma'had Tahfizh Uswah Hasanah, located in Ciledug, Tangerang City. Along with the growth in the number of students, which currently reaches 120 students, the Islamic boarding school has developed internal business units, namely a student laundry unit and a minimarket. The first problem is that, to this day, the laundry soap needs have depended on external parties and the use of conventional detergents containing synthetic chemicals such as ABS (alky benzene sulphonate), a harsh surfactant that is non-biodegradable, thus potentially polluting the water (Suryani & Fitria, 2020). The second problem is that the boarding school does not yet have an integrated accounting application system to record and manage financial transactions. To address these two problems, the PKM team provided appropriate technology, namely a soap mixer machine with green cleaning raw materials. The second was accounting digitalisation in the form of Accurate Desktop, to ensure accurate and transparent financial records. The results of the activity showed an improvement in the knowledge and skills of the pesantren staff and students, both in producing green cleaners and in implementing accounting digitalisation. Thus, this activity contributed to increasing economic independence, operational efficiency, and environmental awareness at Ma'had Tahfixh Uswah Hasanah.